Literasi Keuangan Sosialisasi Keuangan Orang Tua Fear of Messing Out Perilaku Keuangan Mahasiswa Akunansi di Kota Batam - Apriliadi Apriliadi; Mortigor Afrizal Purba (Economic Reviews Journal, 2026)
This research aims to examine and analyze the influence of financial literacy, parental financial socialization, and fear of missing out (FoMO) on the financial behavior of accounting students in Batam City. The population in this study consists of accounting program students at various universities in Batam City. The sampling technique utilized a purposive sampling method with a total sample of 100 respondents. Data collection was conducted by distributing online questionnaires (Google Form) using a Likert scale. The data analysis method employed was multiple linear regression analysis, processed using SPSS version 25 software. The partial research results indicate that financial literacy has a positive and significant effect on financial behavior. Parental financial socialization also exerts a positive and significant influence on financial behavior. Furthermore, fear of missing out (FoMO) significantly and positively affects students' financial behavior. The coefficient of determination (Adjusted $R^2$) shows that the independent variables in this study explain 53.7% of the variance in financial behavior, while the remaining 46.3% is explained by other factors outside this research model.